Investigating the impact of visual perspective in a motor imagery-based brain-robot interaction: A pilot study with healthy participants - Farabbi, Andrea; Figueiredo, Patricia; Ghiringhelli, Fabiola; Mainardi, Luca; Sanches, Joao Miguel; Moreno, Plinio; Santos-Victor, Jose; Vourvopoulos, Athanasios (Frontiers in Neuroergonomics, 2023)
Motor Imagery (MI) based Brain Computer Interfaces (BCI) have raised attention in rehabilitation therapies since they allow to control an external device just using brain activity, in this way promoting brain plasticity mechanisms. However, it is still not clear whether different types of feedback may affect the elicited brain response and hence the effectiveness of MI-BCI for rehabilitation. In this paper we compare two feedback strategies based on controlling the movement of a robotic arm in a MI-BCI system: 1) first-person perspective, whereby the robot arm movement is shown on a screen; and 2) third-person perspective, whereby the subjects observe the robot moving in front of them. We studied 10 healthy subjects over three consecutive sessions The electroencephalographic (EEG) signal was recorded, and the brain response was evaluated in terms of the power of the sensorimotor rhythms, as well as their lateralization, and spatial distribution. Our results show that both feedback perspectives can elicit responses, but without any significant differences between them. Moreover, the evoked responses remained consistent across all sessions, showing no significant differences between the first and the last session. Overall, these results suggest that the type of perspective may not influence the brain responses during a MI BCI task based on a robotic feedback, nonetheless, due to the limited sample size, more evidence is required. Finally, this study resulted into the production of 180 labeled MI EEG datasets, freely available for research purposes.